The soil organic carbon stabilization potential of old and new wheat cultivars: a 13CO2-labeling study - M. Van de Broek; S. Ghiasi; C. Decock; C. Decock; A. Hund; S. Abiven; C. Friedli; C. Friedli; R. A. Werner; J. Six (Biogeosciences, 2020)
Over the past decades, average global wheat yields have increased by about 250 %, mainly due to the cultivation of high-yielding wheat cultivars. This selection process not only affected aboveground parts of plants, but in some cases also reduced root biomass, with potentially large consequences for the amount of organic carbon (OC) transferred to the soil. To study the effect of wheat breeding for high-yielding cultivars on subsoil OC dynamics, two old and two new wheat cultivars from the Swiss wheat breeding program were grown for one growing season in 1.5 m deep lysimeters and pulse labeled with 13CO2 to quantify the amount of assimilated carbon that was transferred belowground and can potentially be stabilized in the soil. The results show that although the old wheat cultivars with higher root biomass transferred more assimilated carbon belowground compared to more recent cultivars, no significant differences in net rhizodeposition were found between the different cultivars. As a consequence, the long-term effect of wheat cultivar selection on soil organic carbon (SOC) stocks will depend on the amount of root biomass that is stabilized in the soil. Our results suggest that the process of wheat selection for high-yielding cultivars resulted in lower amounts of belowground carbon translocation, with potentially important effects on SOC stocks. Further research is necessary to quantify the long-term importance of this effect.